Light emission from hydrogenated and unhydrogenated Si-nanocrystal/Si dioxide composites based on PECVD-grown Si-Rich Si oxide films - Comedi, David Mario (2006)
Hydrogenated and unhydrogenated Si-nanocrystal/Si dioxide (Si-nc/SiO2) composites were obtained from SiyO1-y (y=0.36, 0.42) thin films deposited by plasma-enhanced chemical vapor deposition. The unhydrogenated composites were fabricated by promoting the Si precipitation through thermal annealing of the films in flowing pure Ar at temperatures up to T=1100oC. Fourier transform infrared spectroscopy (FTIR) and elastic recoil detection analysis (ERDA) did not detect any trace of H in these samples. The hydrogenated composites were obtained from identical films by replacing the Ar with (Ar+5%H2) in the annealing step. The photoluminescence (PL) of the composites was studied as a function of the annealing temperature, annealing time and pump laser power. The PL intensity in the Ar-annealed samples increases with increasing annealing temperature, and it increases and then tends to saturation as a function of the annealing time at 1100oC. For the samples annealed in (Ar+5%H2), a qualitatively similar behavior is observed, however, the PL intensity is several hundreds percent larger. The FTIR spectra show that H in these samples incorporates as Si-H bonds. The analysis of the Si-H stretching band, in conjunction with results from previous studies of the Si/SiO2 phase separation process, suggests that a fraction of these bonds are located in the Si/SiO2 interface regions. The dependence of the PL spectra on y, T, and laser power are consistent with the assumption that light emission in both hydrogenated and unhydrogenated Si-nc/SiO2 composites originates from bandgap transitions involving electron quantum confinement in the Si-ncs, the details of the recombination mechanism still being unclear. The PL spectra from the hydrogenated films are skewed to the red as compared to those from the unhydrogenated ones. The bulk of the data indicates that H passivates nonradiative recombination centers, mostly probably Si dangling bonds in the Si-nc/SiO2 regions, thus increasing the number of Si-ncs that contribute to the PL and modifying the distribution of emission wavelengths. The PL intensity in the Ar-annealed samples increases with increasing annealing temperature, and it increases and then tends to saturation as a function of the annealing time at 1100oC. For the samples annealed in (Ar+5%H2), a qualitatively similar behavior is observed, however, the PL intensity is several hundreds percent larger. The FTIR spectra show that H in these samples incorporates as Si-H bonds. The analysis of the Si-H stretching band, in conjunction with results from previous studies of the Si/SiO2 phase separation process, suggests that a fraction of these bonds are located in the Si/SiO2 interface regions. The dependence of the PL spectra on y, T, and laser power are consistent with the assumption that light emission in both hydrogenated and unhydrogenated Si-nc/SiO2 composites originates from bandgap transitions involving electron quantum confinement in the Si-ncs, the details of the recombination mechanism still being unclear. The PL spectra from the hydrogenated films are skewed to the red as compared to those from the unhydrogenated ones. The bulk of the data indicates that H passivates nonradiative recombination centers, mostly probably Si dangling bonds in the Si-nc/SiO2 regions, thus increasing the number of Si-ncs that contribute to the PL and modifying the distribution of emission wavelengths.